Is the Memory Effect of the Blind Spot Involved in Negative Dysphotopsia after Cataract Surgery? - Martin Wenzel; Rupert Menapace; Timo Eppig; Achim Langenbucher (Journal of Ophthalmology)
We present novel clinical observations on negative dysphotopsia (ND) in eyes that have undergone cataract surgery. In the past, shadow effects were alleged to be located in the far peripheral temporal visual field 50° to 100° away from the optical axis. In a small series of eight patients we found evidence of photic effects, described by the patients as shadows in the periphery that were objectively located much more centrally. In all cases, we could find an association of these phenomena with the blind spot. We hypothesize that the memory effect of the blind spot which is dislocated and changed in magnification due to replacement of the crystalline lens could be one determinant for pseudophakic ND. The scotoma of the optic nerve head and the main arteries and veins of the phakic eye are displaced in the pseudophakic eye depending on the specific characteristics and position of the intraocular lens within the eye.